Estimation of gross-structure parameters of giant dipole resonance: 1. A method - Uvarov, V.L.; Zakharchenko, A.A. (Вопросы атомной науки и техники, 2021)
Available data on photonuclear cross-sections, both measured experimentally and obtained on the basis of theoretical models, are characterized sometimes by a considerable spread. In work, a simple method for the estimation of width (FWHM) and maximum (σₘₐₓ) of excitation function of a reaction with dominant giant dipole resonance, is given. An analytical model is developed for the description of isotope production in an X-ray beam. It is shown, that the established yield of the reaction in a thin target, overlapping completely the beam with known end-point photon energy makes it possible to estimate the σₘₐₓ and FWHM values. The possibilities of new approach are demonstrated by a numerical experiment on the reference reactions.